Modeling Life-Cycle Earnings Risk with Positive and Negative Shocks - Manuel Sanchez; Felix Wellschmied (Institute of Labor Economics (IZA), 2017)
We study workers' idiosyncratic earnings risk over the life-cycle using a German administrative data set. Positive and negative earnings shocks both contain a highly persistent component. The variance and average size of positive persistent shocks is decreasing over the life-cycle. The (absolute) size of negative persistent shocks is increasing. The probability to experience either of these shocks is U-shaped in age; during prime-age it is around 35 percent. Negative transitory shocks are relatively larger and more dispersed than positive transitory shocks. Their size and variance are increasing over the life-cycle. Large persistent positive shocks early in life generate large wealth holdings for the top one percent of workers in an incomplete markets model. Moreover, age-varying risk implies a linear increase in consumption inequality late in working life.
Keywords: E21; E24; J31; 330; life-cycle; earnings risk; wealth dispersion